Experiments to investigate direct containment heating phenomena with scaled models of the Surry Nuclear Power Plant - Blanchat, T. K.; Allen, M. D.; Pilch, M. M.; Nichols, R. T. (U.S. Nuclear Regulatory Commission. Office of Nuclear Regulatory Research. Division of Systems Research., 1994)
The Containment Technology Test Facility (CTTF) and the Surtsey Test Facility at Sandia National Laboratories are used to perform scaled experiments that simulate High Pressure Melt Ejection accidents in a nuclear power plant (NPP). These experiments are designed to investigate the effects of direct containment heating (DCH) phenomena on the containment load. High-temperature, chemically reactive melt (thermite) is ejected by high-pressure steam into a scale model of a reactor cavity. Debris is entrained by the steam blowdown into a containment model where specific phenomena, such as the effect of subcompartment structures, prototypic air/steam/hydrogen atmospheres, and hydrogen generation and combustion, can be studied. Four Integral Effects Tests (IETs) have been performed with scale models of the Surry NPP to investigate DCH phenomena. The 1/61{sup th} scale Integral Effects Tests (IET-9, IET-10, and IET-11) were conducted in CTRF, which is a 1/6{sup th} scale model of the Surry reactor containment building (RCB). The 1/10{sup th} scale IET test (IET-12) was performed in the Surtsey vessel, which had been configured as a 1/10{sup th} scale Surry RCB. Scale models were constructed in each of the facilities of the Surry structures, including the reactor pressure vessel, reactor support skirt, control rod drive missile shield, biological shield wall, cavity, instrument tunnel, residual heat removal platform and heat exchangers, seal table room and seal table, operating deck, and crane wall. This report describes these experiments and gives the results.